Circulating Resistin Is Associated with Plasma Glucagon-Like Peptide-1 in Cirrhotic Patients with Hepatitis C Virus Genotype-4 Infection. (2nd January 2020) - Ibrahim, Doaa M.; Shaaban, El Saeid E.; Fouad, Tarek A.
ABSTRACT: Purpose : Limited and contradictory data on the circulating levels of glucagon-like peptide (GLP-1) and resistin in hepatitis C virus genotype-4 (HCV-4) cirrhotic patients are present. Thus, this study aimed to evaluate their concentrations and to investigate the association between total GLP-1, resistin, and insulin resistance in those patients. Materials and Methods : Non-diabetic HCV-4 cirrhotic patients (n = 80; 40 with Child-Pugh A, 20 with Child-Pugh B, and 20 with Child-Pugh C), and 25 healthy subjects were enrolled in this study. The basal circulating levels of total GLP-1 and resistin along with serum insulin, glucose, total cholesterol, and triglycerides were measured. Results : Plasma GLP-1 and serum resistin levels were significantly higher in cirrhotic patients than controls ( P < . 001). Moreover, circulating GLP-1 and resistin levels increased in a stepwise fashion in line with increasing grade of liver damage. According to Spearman's rank correlation, both GLP-1 and resisitin correlated positively with each other, insulin, homeostatic model assessment of insulin resistance, alanine aminotransferase (ALT), total bilirubin, and international normalized ratio while they correlated negatively with albumin ( P < .001). Multiple stepwise regression analysis showed that ALT, serum resistin and Child-Pugh score independently influenced the GLP-1 levels in cirrhotic patients. Conclusions : Circulating levels of GLP-1 and resistin were elevated in cirrhotic patients with HCV-4. Further, the severity of liver cirrhosis and serum resistin were the determinant factors explaining the variability of GLP-1 levels by about 84%. In addition, a positive relation was found between insulin resistance and both GLP-1 and resistin levels.